Utilization Pattern, Distribution, and Tree Diversity of Betalghat Block, Nainital District (Western Himalaya) (Global Journal of Science Frontier Research, 2018)
The Himalayan region is the repository of socio-cultural and biological diversity with high valued plants. Participatory Rural Appraisal (PRA) tools were used to document the diversity, distribution and utilization pattern of trees in the Betalghat Block of Nainital District (Western Himalaya). A total of 148 species belongs to 109 genera, and 50 families were recorded from the study area. Maximum numbers of species were reported in the altitudinal zone 1001-1500m followed by the altitudinal zone, 500-1000m. Fabaceae, Moraceae,
Keywords: trees; diversity; distribution; utilization pattern; PRA tools; betalghat